Overtraining, recovery and central fatigue - Meeusen, R. (First international symposium sciences and practices in swimming, 2006)
The human body has the capacity to adapt to various forms of stressful Stimuli. From a physiological standpoint, exercise can impose a significant amount of stress on an organism. Muscular activity requires coordinated Integration of many physiological and biochemical Systems. Such Integration is possible only if the body's various tissues and Systems can communicate with each other. The nervous System is responsible for most of this communication through central command and peripheral adjustements. The endocrine and nervous System work in concert to initiate and control movement and all physiological processes it involves. When all facets of the central nervous and neuro endocrine System are performing in harmony, the ability to coordinate and regulate key physiological and metabolic functions, under the perturbations imposed by physical exercise, is quite remarkable. Regular exercise or training will result in better performance, however this 'challenge of homeostasis' can lead to a disturbed balance between training and recovery. In overtrained athletes, several signs and Symptoms have been associated with this imbalance between training and recovery. However, reliable diagnostic markers for distinguishing between well-trained, overreached and overtrained athletes are lacking. Recently the European College of Sports Medicine developed a consensus Statement where a distinction between Functional overreaching, Non Functional Overreaching and the Overtraining syndrome is made. A hallmark feature of overtraining syndrome (OTS) is the inability to sustain intense exercise and recover for the next training or competition Session. The Symptoms associated with overtraining, such as changes in emotional behaviour, sleep disturbances, and hormonal dysfunctions are indicative of changes in the regulation and coordinative function of the hypothalamus. In pathological situations such as in major depression and also in overtraining, the glucocorticoids and the brain monoaminergic systems apparently fail to restrain the (Hypothalamic Pituitary Adrenal axis) HPA response to stress. To date, relatively little attention has been placed on the role of the central nervous System in overtraining and fatigue during exercise and training. We will focus on the the role of neurotransmitters and neuromodulators in mechanisms that underly overtraining.